Running economy and mechanics in triathletes vs. runners - Takahashi, K.; Usui, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to compare running economy (RE) and distance running mechanics between triathletes and runners to examine an energy-economical running form. Physiological measures were obtained, including maximal and submaximal 02 consumptions and blood lactate concentration. Biomechanical measures for running at several speeds (210-290 mlmin) were obtained for the triathletes and runners. The RE in the triathletes was higher than that in the runners at most speeds (210-270 mlmin). The maximal angle of shoulder extension was associated with RE and greater in the triathletes at lower speeds (21 0-250 mlmin). The training and running form of triathletes are potentially useful for improving the RE in runners.